Study of cell irregularity effects on the compression of closed-cell foams. (January 2018) - Shi, Xiaopeng; Liu, Shuangyan; Nie, Hailiang; Lu, Guoxing; Li, Yulong
Highlights: The reduced elastic modulus increases a little with increasing regularity of the Voronoi foams while the plastic-collapse stress increases significantly. Theoretical model revealed that irregularity causes more severe deformation when the foam is compressed under the same force. Both the initial peak stress and the plateau stress of the foam increase with the increasing loading velocity and relative density of the foam, but the foams with low regularity show relative lower rate sensitivity on initial peak stress. Abstract: Closed-cell aluminum foam is widely used as energy absorbing material. The cell regularity profoundly affects the mechanical behavior of this material. To investigate the influence of irregularity on elastic and plastic behavior of closed-cell foams, the compression behavior of Voronoi foams was simulated using the finite element method. The results show that with the increasing randomness of the foam, the elastic modules decrease a little while the collapse-strength decrease considerably. A theoretical analysis is conducted with the simple springs model. The results match well with simulation which shows theoretical analysis is reasonable. The Voronoi models were also compressed under different loading velocities and with different relative densities in simulation. The results reveal that foams with low regularity are more suitable for application in protective structures. Graphical abstract: Image, graphical abstract